Ekspresi Dakwah Mahasiswi Ilmu Hadis UIN Sultan Syarif Kasim Riau di TikTok Perspektif Hadis - Adynata, Adynata; Aprianti, Sindy; Yeli, Salmaini; Ma'ali, Dasman Yahya (UIN Sultan Syarif Kasim Riau, 2023)
The popularity of the TikTok application has garnered attention due to its content, which has been proven to capture the interest of internet users. These contents are uploaded and widely disseminated in the online world, reaching thousands of internet users. TikTok, in addition to being entertainment, serves as a platform for various purposes such as self-expression, promotion, education, and religious propagation. The aim of this research is to understand the motivations of female students in creating TikTok content and the types of content they produce and to evaluate them from the perspective of hadith. The research question is how the hadith perspective views the expression content of female students at the State Islamic University Sultan Syarif Kasim Riau on TikTok on their respective accounts and what motivates them. This research involves field research and library research using a mixed-method approach. In data collection, the researcher uses observation, interviews, and documentation techniques. The findings of this research are as follows: First, there are various motivations among female students in the Hadith Studies Program at UIN Sultan Syarif Kasim Riau to create content, such as religious propagation, knowledge sharing, and leisure. Second, there are two types of content created by female students in the Hadith Studies Program, namely content that adheres to Sharia, such as Islamic propagation, education, and motivation. Additionally, there is content that contradicts Sharia, containing elements of revealing aurat (intimate parts) and tabarruj (excessive adornment), ikhtilath (intermingling of genders), and tasyabbuh (resembling a particular group). In the hadith perspective, content that adheres to Sharia is seen as promoting goodness and will be a continuous reward for the content creator. On the other hand, content that contradicts Sharia is considered to promote wrongdoing and will result in a continuous sin for the content creator. Abstrak: Popularitas aplikasi TikTok mendapat sorotan karena konten yang disajikan terbukti mampu menarik perhatian para pengguna internet. Konten-konten tersebut diupload dan tersebar luas di dunia maya sehingga disaksikan oleh ribuan pengguna internet. Tiktok, di samping sebagai hiburan juga menjadi media untuk berbagai kepentingan seperti berekpresi, promosi, pendidikan, dakwah dan lain sebagainya. Tujuan dari penelitian ini adalah untuk mengetahui motivasi mahasiswi dalam pembuatan konten Tiktok, jenis-jenis konten yang dibuat dan tinjauannya dilihat dari perspektif hadis. Sedangkan rumusan masalah adalah bagaimana perspektif hadis terhadap konten ekspresi mahasiswi Universitas Islam Negeri Sultan Syarif Kasim Riau di Tiktok pada akun-akun mereka serta motivasinya. Jenis penelitian ini merupakan penelitian lapangan (field research) dan studi pustaka (library research) dengan menggunakan metode campuran. Dalam pengumpulan data, peneliti menggunakan teknik observasi, wawancara dan dokumentasi. Adapun hasil dari penelitian ini yaitu, Pertama, terdapat beragam motivasi mahasiswi Program Studi Ilmu Hadis UIN Sultan Syarif Kasim Riau dalam pembuatan konten, seperti berdakwah, berbagi ilmu dan mengisi waktu luang. Kedua, terdapat dua jenis konten yang dibuat oleh mahasiswi Program Studi Ilmu Hadis yaitu konten yang sesuai dengan syari’at berupa konten dakwah Islam, edukasi dan motivasi. Selain itu ada juga konten yang bertentangan dengan syari’at berupa konten yang mengandung unsur menampakkan aurat dan tabarruj, ikhtilath (campur baur) serta tasyabbuh (menyerupai suatu kaum). Adapun dalam tinjauan hadis konten yang sesuai dengan syari’at berisi tentang kebaikan akan menjadikan pahala jariyah bagi pembuat konten, sedangkan konten yang bertentangan dengan syari’at berisi tentang keburukan akan menjadikan dosa jariyah bagi pembuat konten.